O desenho como forma de comunicação da arquitetura - Martins, Cláudia Alonso (2013)
Architects draw to present their projects. To demonstrate, through experiments charts their projects, they run through several forms of representation derived from geometric systems and tooling. Their procedures resort to various tooling and supports, and produce different representations. The answers to the questions of how the architects present their projects are the guiding thread of this study. The goal is to achieve answers to the problems that permeate the communicated representation and elaborate through the design of architecture. Understand and learn the drawings used by architects as a means of reflection and communication. The ways in which the design operates architecture and urbanism are forms of reflection and thought. In the case of architecture are the means of object creation and communication that enable its implementation or construction. Other abstract records can also be used as schemas, tables, figures or diagrams that allow other procedural and communication strategies. When dealing with contemporary modes of presentation of projects and having as object significant projects of contemporary, were elected for this study three projects representing different periods, namely: the Parc de La Villette, Paris, France, Bernard Tschumi (1983), the McCormick Tribune Campus Center at the Illinois Institute of Technology in Chicago, USA, OMA / Rem Koolhaas (2003) and the 8House in Ørestad, Denmark, the BIG Bjarke Ingles Group (2010). Through close reading of these projects in parallel with the speech intended to representations of the same by their authors, and by understanding and using graphics engines for interpretation, this work studied how they were intended to present their proposals and procedures of design that were used for this purpose . The drawings were analyzed seeking to deepen all the elements and processes involved in the determination and communication of data represented.